MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV MELALUI PENERAPAN STRATEGI GUIDED NOTE TAKING PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI MI MATLA'UL ATFAL - Najwa Zamzami Nurdin, Salmatun; Titim Fatimah; Muhammad Rifqi Mahmud (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by the low critical thinking skills of fourth-grade students at MI Matla'ul Atfal in Pancasila Education subject. The purpose of this study was to determine the difference in improvement of students' critical thinking skills between the experimental class applying Guided Note Taking strategy and the control class applying Cooperative Learning strategy. The research method used wae quasi-experimental with Nonequivalent Control Group Design. The population was all fourth-grade students at MI Matla'ul Atfal with samples of class IV A (15 students) as experimental class and class IV B (14 students) as control class using purposive sampling technique. Research instruments were pretest-posttest essay tests and learning activity observation sheets. Data analysis used Shapiro-Wilk normality test, homogeneity test, independent t-test, and Mann Whitney test. eesults showed the average pretest score of experimental class was 68.17 and control class 55.14, while the average posttest score of experimental class was 77.17 and control class 52.50. Mann Whitney test results showed sig. (2-tailed) value of 0.000 < 0.05, thus H₀ was rejected. The N-Gain value of experimental class was 0.29 (low category) higher than control class -0.07 (decrease occurred). In conclusion, the implementation of Guided Note Taking strategy can improve the critical thinking skills of fourth-grade students in Pancasila Education subject at MI Matla'ul Atfal.